Lightweight dynamic model for fusion of three-dimensional surface–stratum underground structures - Cuiying Zhou; Yusen Zhong; Ziyu Tao; Chunhui Lan; Wei Hu; Zhen Liu (PLoS ONE, 2025)
Three-dimensional visual modeling of surface-stratum-structure is an inevitable requirement for intelligent geotechnical engineering. However, the heterogeneity of surface, stratigraphic and structural data sources and modeling methods leads to incompatibility of model attributes. Only a few studies have directly realized the three-dimensional (3D) modeling of surface-strata-structure. In order to solve this problem, this study uses the Kriging interpolation method based on relative elevation to realize the fusion of borehole data and surface data, and establishes a 3D surface-strata model. The Boolean difference set operation based on the bounding box method is used to propose a geometric fusion method for the 3D surface-strata-underground structure model. In addition, an attribute fusion method of 3D surface-stratum-underground structure model is introduced by using variable storage method. Finally, this study established a comprehensive 3D model of surface-strata-underground structure. Considering the characteristics of the fusion model, the dynamic expression of the 3D settlement model is realized, and a lightweight processing method using layered rendering technology is proposed, which is helpful to establish a lightweight 3D dynamic model of surface-strata-underground structure. The feasibility and reliability of the above method are verified by engineering application analysis. The main contributions of this method include simplifying the integration process of surface, stratum and structure models, which may enhance the modeling of integrated engineering information.